Synthesis and structure elucidation of some new thioether derivatives of 1,2,4-triazoline-3-thiones and their antimicrobial activities - (:unkn) unknown (ELSEVIER SCIENCE SA, 2001)
5-(4-Pyridinyl)-4-substituted-2,4-dihydro-3H-1,2,4-triazole-3-thiones and 5-(4-pyridinyl)-4-substituted-3-(benzoylmethyl)thio 4H-1,2,4-triazoles were synthesized. The structures of original nine compounds were confirmed by IR, H-1 NMR, mass spectral methods and elemental analysis. The antibacterial, antifungal and antimycobacterial activities, together with those of known intermediate 1,4-disubstituted thiosemicarbazides, were reported. (C) 2001 Elsevier Science S.A. All rights reserved.
Keywords: 1,2,4-triazole derivatives; synthesis; antibacterial, antifungal; antimycobacterial activities; ANTIFUNGAL ACTIVITIES; ANTIBACTERIAL; THIOSEMICARBAZIDES; ANTIMYCOBACTERIAL